[18F]fluorocholine PET vs. [99mTc]sestamibi scintigraphy for detection and localization of hyperfunctioning parathyroid glands in patients with primary hyperparathyroidism: outcomes and resource efficiency - Rep Sebastijan; Sirca Klara; Lezaic Ema Macek; Zaletel Katja; Hocevar Marko; Lezaic Luka (Radiology and Oncology)
Minimally invasive parathyroidectomy is the treatment of choice in patients with primary hyperparathyroidism (PHP), but it needs a reliable preoperative localization method to detect hyperfunctioning parathyroid tissue. Higher sensitivity and lower radiation exposure was demonstrated for [18F]fluorocholine PET/CT (FCh-PET/CT) in comparison to [99mTc]sestamibi (MIBI) scintigraphy. However, data of its efficiency in resource use and patient outcomes is lacking. The aim of our study was to determine the resource efficiency and patient outcomes of FCh-PET/CT in comparison to conventional MIBI scintigraphy.